Mali : Enhanced Initiative for Heavily Indebted Poor Countries-Completion Point Document. (IMF Staff Country Reports; Country Report ;, 2003)
This paper assesses Mali's progress under the Heavily Indebted Poor Countries (HIPC) Initiative, and seeks Board approval of the completion point under the enhanced framework. By end-December 2002, the policy reforms for the floating completion point under the enhanced HIPC Initiative had been implemented satisfactorily. These included macroeconomic stability, structural reforms, and social sector programs. IMF staff is of the view that Mali's performance with respect to the conditions for reaching a completion point under the enhanced HIPC Initiative has been satisfactory.